Antimicrobial resistance: Examining the environment as part of the one health approach - Mirza Alas (South Centre, 2020)
Antimicrobial Resistance (AMR) is a serious issue that is threatening the medical and agricultural advances of today. The connections that exist among human health, food production and the environment necessitate a One Health approach to address the challenge of AMR. Recent research points to the environment as an essential factor in the spread of AMR, as well as a possible reservoir of antimicrobial resistant bacteria and genes. The process, however, of the environmental transmission of resistance genes, along with their effects and how to mitigate them, is still being examined. As new research emerges, so to have new challenges regarding the selective pressure of antibiotics on the environment. AMR in the environment is not new, with resistance genes found even in isolated places (e.g. in permafrost or volcanoes) but understanding this natural process and its implications for tackling AMR continue to pose many questions. This paper aims to examine some of the emerging research on AMR from a One Health perspective and in particular to highlight the role of the environment. It will explore the use of antibiotics and their effects in different ecosystems, as well as the challenges they pose for developing countries: in particular, in designing policies to address antimicrobial resistance that take into account the connections among humans, animals and the environment.
Keywords: 300; Action on Antibiotic Resistance (ReAct); Agriculture; Animals; Antibiotics; Antimicrobial Resistance (AMR); Aquatic Environment; Environment; Farms; Food and Agriculture Organization (FAO); Food Production; Health; Hospitals; Microbiota; One Health Approach; United Nations Children's Fund (UNICEF); United Nations Environment Programme (UNEP); Waste Management; WHO; World Health Organization (WHO); World Organisation for Animal Health (OIE)